Post-Disaster in Lombok and Social Entrepreneurship - Ihwana As’ad; Muh. Nur Fithri,T (Simposium Antar Bangsa Seminar dan Workshop)
Natural disaster, one of nature phenomenon that hardly predicted and became part of human being life. Disaster in recent time already occured almost everywhere and spread throughout Indonesia, especially in certain location where people can experience it directly. The damage caused by disaster and bring disadvantages either in material form or nonmaterial form. From this disaster, sympathy can be raised to help those people involved. Resurrection is not easy thing, some concepts are offered to clear the trauma, loss, and dependence on other site in making solutions. In this paper, one of solution offered to resurrect is Social Entrepreneurship concept, might be the key for resurrecting in certain damaged location. This social entrepreneurship concept can be tourism, skill industry, handicraft, and culinary.